Analysis, Synthesis and Characterization of Thin Films of a-Si:H (n-type and p-type) Deposited by PECVD for Solar Cell Applications - Abel Garcia-Barrientos (MDPI AG, 2021)
In this paper, the analysis, synthesis and characterization of thin films of a-Si:H deposited by PECVD were carried out. Three types of films were deposited: In the first series (00 process), an intrinsic a-Si:H film was doped. In the second series (A1–A5 process), n-type samples were doped, and to carry this out, a gas mixture of silane (SiH4), dihydrogen (H2) and phosphine (PH3) was used. In the third series (B1–B5 process), p-type samples were doped using a mixture of silane (SiH4), dihydrogen (H2) and diborane (B2H6). The films’ surface morphology was characterized by atomic force microscopy (AFM), while the analysis of the films was performed by scanning electron microscopy (SEM), and UV–visible ellipsometry was used to obtain the optical band gap and film thickness. According to the results of the present study, it can be concluded that the best conditions can be obtained when the flow of dopant gases (phosphine or diborane) increases, as seen in the conductivity graphs, where the films with the highest flow of dopant gas reached the highest conductivities compared to the minimum required for materials made of a-Si:H silicon for high-quality solar cells. It can be concluded from the results that the magnitude of the conductivity, which increased by several orders, represents an important result, since we could improve the efficiency of solar cells based on a-Si:H.